2013
DOI: 10.1108/17542731311299564
|View full text |Cite
|
Sign up to set email alerts
|

MBNQA criteria used in the GCC countries

Abstract: Purpose -Quality criteria of The Malcolm Baldrige National Quality Award (MBNQA) have been used as a standard for organisational self-assessment and benchmarking. The threefold purpose of this paper is: to analyse the individual weights of the MBNQA criteria for organisations of the construction and the manufacturing industry within the GCC (Gulf Cooperation Council) countries in order to create a basis for self-assessment and benchmarking; to identify differences of criteria importance between the constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…These results are consistent with Zairi (1996) and Garza-Reyes et al (2011), who claimed that Kuwaiti industries are still in the early stages of understanding and using quality initiative, as well as Al-khalifa and Aspinwall (2000), who suggested that the maturity level towards quality initiative is very low in Arabic countries, and with Jaeger et al (2013), who said that quality initiative does not play an important role in Gulf Cooperation Council (GCC) organizations. Moreover, this result proves the findings of Tannock and Ahmed (2008), who found that Arab countries have yet to feel pressure to implement quality initiative.…”
Section: Top Management and Leadershipsupporting
confidence: 85%
“…These results are consistent with Zairi (1996) and Garza-Reyes et al (2011), who claimed that Kuwaiti industries are still in the early stages of understanding and using quality initiative, as well as Al-khalifa and Aspinwall (2000), who suggested that the maturity level towards quality initiative is very low in Arabic countries, and with Jaeger et al (2013), who said that quality initiative does not play an important role in Gulf Cooperation Council (GCC) organizations. Moreover, this result proves the findings of Tannock and Ahmed (2008), who found that Arab countries have yet to feel pressure to implement quality initiative.…”
Section: Top Management and Leadershipsupporting
confidence: 85%
“…In relation to the respondents" educational profile, Table 2 indicates that the respondents are well educated and that the targeted health centers have an interest in educational qualifications for their managers and employees. (26) were middle management employees and 7.6 % (7) of them were leadership. Finally, Table 2 shows that the respondents had a good level of experience, where the majority of them (57.7%) having more than 5 years experience in their centers.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…The study confirmed the variability in the principles used in different countries and regions due to many influencing factors, such as religion, culture, education level, information technology, government regulations, and the extent of industrialization. A more regionally related study, conducted by Jaeger et al (2013), presented the ranking of quality criteria used in the Gulf Cooperation Council countries, based on the MBNQA model. The most common principles, as reported by Besterfield et al (2003), and supported by Sousa and Voss (2002), Motwani (2001), Agus and Abdullah (2000), are leadership commitment, employee involvement, customer focus, supplier relationship, performance measurement, and continuous improvement.…”
Section: Introductionmentioning
confidence: 99%